THE ECONOMIC EMPOWERMENT PROGRAMMES OF MOUNTAIN OF FIRE AND MIRACLES MINISTRIES IN LAGOS STATE, NIGERIA (2023)
Economic Empowerment Programmes (EEPs), which refer to the response of non-governmental and faith-based organisations to the issues of poverty and unemployment, are central to the operations of Mountain of Fire and Miracles Ministries (MFM). Previous studies on EEPs in Nigeria concentrated largely on empirical relationship between government intervention programmes and poverty alleviation, the European Union and United Nations Millennium Development Goals, with little attention paid to the inputs made by faith-based organisations. This study was, therefore, designed to examine the EEPs of MFM, with a view to determining the form of EEPs, their strategies, impact and challenges in Lagos State, Nigeria. Robert Barro’s Religious Facilitating Economic Empowerment Theory was used as the framework, while the descriptive design was adopted. Purposive sampling was used to select Alimosho, Agege, Amuwo-Odofin, Ikorodu and Lagos-mainland in Lagos State. These were the five places where the MFM’s EEPs were actively and prominently executed. In-depth interviews were conducted with 130 purposively selected respondents: 10 Programme Coordinators (PCs), 25 Pastors, 15 Church members and 80 EEPs beneficiaries. Five sessions of focus group discussions were conducted: two sessions with 10 PCs, one session with five pastors, and two sessions with 15 beneficiaries, comprising (10 men and 20 women). The data were content-analysed. Three EEPs were identified: skill acquisition, financial scheme and vocational empowerment; and four strategies (vocational training, provision of loans, financial grants and distribution of vocational materials) were adopted in executing the programmes. Skill acquisition employed a vocational training strategy to reach out to 553 farmers, 505 fashion designers, 204 caterers, 301 information technologists, 105 food processors, 264 leather processors and 106 bag makers. Financial scheme deployed a provision of 5% interest loan in the range of N50,000.00 to N500,000.00 and reached out to 120 certified applicants. Also, financial scheme adopted the financial grants method and gave out N24,000,000.00 to 80 merchants and 40 retailers. They claimed that the grants were spent to expand their businesses and pay outstanding shop rents. Also, N8,000,000.00 was given to 80 widows to start their 80 poultry businesses. Vocational empowerment used a vocational materials strategy to reach out to 554 certified beneficiaries: 356 industrial sewing machines, 104 leather sewing machines, 20 soap mixers, 42 catering materials, six bead stoning machines, five cameras, three laptops, two photocopiers, 10 food grinding and processing machines, and six cloth dryers. Through the skill acquisition programme, the rate of unemployment among the church members was reduced from 4,850 to 2,038. The financial scheme programme relieved the beneficiaries of depending on the church for their means of livelihood. The vocational empowerment programme promoted financial autonomy for the concerned MFM members. However, inconsistent follow-up of trainees, non-repayment of loans, mismanagement of funds and selling off of empowerment materials by some beneficiaries were reported as major challenges confronting the execution of each of the EEPs. The Mountain of Fire and Miracles Ministries has contributed to reducing the problem of poverty and unemployment in the Nigerian government through its economic empowerment programmes in Lagos State, Nigeria.